2011
DOI: 10.1128/jb.05501-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Nonpathogenic Listeria monocytogenes Serovar 4a Strain M7

Abstract: This report presents the complete and annotated genome sequence of the naturally nonpathogenic Listeria monocytogenes serovar 4a strain M7, isolated from cow's milk in Zhejiang province, China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…The genomes of several strains of L. monocytogenes have been sequenced in recent years (9,(19)(20)(21)(22). At present, there are 34 L. monocytogenes genomes publicly available, of which 16 are finished and 18 are available as draft sequences.…”
mentioning
confidence: 99%
“…The genomes of several strains of L. monocytogenes have been sequenced in recent years (9,(19)(20)(21)(22). At present, there are 34 L. monocytogenes genomes publicly available, of which 16 are finished and 18 are available as draft sequences.…”
mentioning
confidence: 99%
“…We found that the M7 strain had apparent phospholipase activity due to high-level expression of PlcB, probably as a result of constitutive activation of PrfA (Chen et al, 2011b). Transcription levels of major PrfA-regulated genes in M7 were higher than in EGDe, both in broth media and in whole blood, while M7 did not cause any lethality to mice and its load in the liver and spleen was far lower than for EGDe.…”
Section: Defects Of the M7 Strain In Virulence-related Phenotypesmentioning
confidence: 86%
“…Sequence analysis has shown that PrfA of the serovar 4a strain M7 from milk has three amino acids (Ser145, Ala165 and Asn197) different from those of EGDe (Gly145, Thr165 and Lys197) (Chen et al, 2011b), indicating that the PrfA of M7 could be constitutively active for transcriptional regulation, seen as strong phospholipase and haemolytic activities (Ripio et al, 1997;Vega et al, 2004;Wong & Freitag, 2004). Transcriptional analysis of PrfA-regulated genes in BHI medium and whole sheep blood showed that M7 did have a significantly higher expression than EGDe (Pv0.01) (Fig.…”
Section: Prfa Of the Low-virulence Strain M7 Was Constitutively Activmentioning
confidence: 99%
See 1 more Smart Citation
“…Leuconostoc pseudomesenteroides KCTC 3652, sequence accession AEOQ00000001 through AEOQ00001160 [61] Lactobacillus mali KCTC 3596, sequence accession BACP01000001 through BACP01000122 [62] Paenibacillus polymyxa Type Strain ATCC 842 T , sequence accession AFOX01000000 [63] Streptococcus salivarius strain JIM8777, sequence accssion FR873482 [64] Lactobacillus cypricasei KCTC 13900, sequence accession BACS01000001 to BACS01000487 [65] Lactobacillus zeae KCTC 3804, sequence accession BACQ01000001 to BACQ101000113 [66] Listeria monocytogenes Serovar 4a Strain M7, sequence accession CP002816 [67] Lactobacillus salivarius GJ-24, sequence accession AFOI00000000 [68] Lactobacillus johnsonii PF01, sequence accession AFQJ01000000 [69] Clostridium acetobutylicum DSM 1731, sequence accession CP002660 through CP002662 [70] Lactobacillus suebicus KCTC 3549, sequence accession BACO01000000 [71] Brevibacillus laterosporus LMG 15441, sequence accession AFRV00000000 [72] Lactobacillus salivarius NIAS840, sequence accession AFMN00000000 [73] Bifidobacterium animalis subsp. lactis CNCM I-2494, sequence accession CP002915 [74] Megasphaera elsdenii, sequence accession HE576794 [75] Lactobacillus versmoldensis KCTC 3814, sequence accession BACR01000001 to BACR01000102 [76] Lactobacillus pentosus IG1, sequence accession FR874848 to FR874860 [77] Alicyclobacillus acidocaldarius Strain Tc-4-1, sequence accession CP002902 [78] Streptococcus thermophilus Strain JIM8232, sequence accession FR875178 [79] Streptococcus equi subsp.…”
mentioning
confidence: 99%